A STUDY ON COMPRESSIVE BEHAVIOR OF REINFORCED CONCRETE COLUMN CONTAINING GRANITE POWDER WASTE - Priyanka, M.; Nizar, N.Mohamed (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
In the era, as a result of growth in infrastructure development and the consequent increase in consumption have led to the fast decline in available natural resources. So that the engineers are constrained to implement new materials and techniques to efficiently develop the conventional concrete. Concrete containing conventional granite powder (GP) waste is showing good mechanical properties such as workability, compressive strength, tensile strength and elastic modulus. However, more investigation is required in order to understand structural behavior of granite powder concrete at the structural member scale. The main objective of this study is to experimentally investigate the compressive behavior of RC column containing granite industry waste and experimental parameter is grade of concrete. Granite waste with the sand replacement of 0% and 15% was used in this experiment. Experiments were undertaken under failure to fully understand the effect granite powder on the cubes and compressive behavior of RC column. From the above observation it is suggested that the concrete with substitution of 15%GP waste can be used in the structural concrete